KOMODIFIKASI SIARAN OLAHRAGA DI TELEVISI PUBLIK: STUDI KASUS LIGA PRIMER INGGRIS DI LPP TVRI - Warapsari, Dhyayi; Rahmiaji, Lintang Ratri; Armando, Ade (Master of Communication Science Program, Universitas Diponegoro, 2021)
Sport and media have a long history of mutually beneficial relationship. Sport has become a commodity. Private televisions use sport programs to gain more profits through various methods, such as advertising and paid subscription. The potential benefits that media can gain from sport have driven the competition between broadcasters to get the broadcasting rights and thus drive the broadcasting rights fees higher every season. In 2019, TVRI with limited annual budget can acquire English Premier League broadcasting rights through partnership with Mola TV. TVRI as a public service broadcaster is not allowed to be profit-oriented like private televisions. This article investigates commodification of sport in Indonesian public television, TVRI, with study case of English Premier League. Data are collected from literature study and observation, then it is analyzed from a political economy perspective. It is found that TVRI use English Premier League to gain more audiences and profits through various sport programs - similar to private televisions, but with some limitations that public television has.